DEVELOPMENT OF PAINTING IN MARATHA AREA: मराठा क्षेत्र में चित्रकला का विकास - Jain, Sushma (International Journal of Research -GRANTHAALAYAH, 2016)
The painting tradition in the Maratha region dates back to prehistoric times. Human beings have left examples of paintings with a very careful reflex of behavior. In the primitive tendons of Madhya Pradesh, we are surprised today by the many linear signs of the human and the aesthetic form of the weapons, following the craving to be cultured and ornate on that barbar. मराठा क्षेत्र में चित्रकला परंपरा का प्रारंभ प्रागैतिहासिक काल से होता है। मानव ने बहुत ही प्रांरभ में व्यवहार की सजगता के साथ चित्रों के उदाहरण छोड़े हैं। मध्यप्रदेश की आदिम कंदराओं में हमें उस बर्बर पर सुसंस्कृत और सुअलंकृत होने की लालसा के अनुगामी मानव के रचे अनेक रेखीय चिन्ह तथा अस्त्र शस्त्रों के सौंदर्य प्रधान रूप आज हमंें आश्चर्य चकित करते है।1